The impact of ownership structure on firm value: New evidence from Thai listed firms (International Journal of Scientific Research and Management (IJSRM), 2023)
This research aimed to examine the impact of ownership structure on firm value based on new evidence from 100 listed companies in Thailand in 2020. Firm value was measured by Tobin’s Q, while ownership structure variables were institutional ownership, local investors’ ownership, family ownership, and government ownership. Multiple regression analysis was used to statistically analyse the data. The results of the study showed that the variable of ownership affecting a firm’s value consisted of institutional ownership, local investors’ ownership, and family ownership. On the other hand, government ownership and foreign ownership did not have an impact on firm values in regards to the proportion of institutional investors, local investors’ ownership and family ownership leading to encouraged corporate governance mechanisms with consequential transparency and reliability. Therefore, a listed company should be aware and pay attention to the proportion of appropriate ownership structure that may affect firm performance leading to an increase in further potential investors.